Rotor Pole Analysis of Various 3 Phase Outer Rotor Hybrid Excitation Flux Switching Motor - Shamsul, Nurhazwani Hadhirah; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2025)
Hybrid Excitation Flux Switching Machine (HEFSM) represent an emerging class of electric machines that integrate both permanent magnets and field windings within the stator, enabling a controllable flux mechanism. Several benefits of this special topology include high power density, efficiency, and wide-band operation. However, the choice of rotor-pole configurations has a big impact on how well HEFSMs work since they control the machine’s electromagnetic properties such torque generation, efficiency, cogging torque, and operational stability. Their employment in vital fields including robotics, electric vehicles (EVs), and renewable energy systems is restricted by issues like excessive cogging torque, torque ripple, and magnetic losses, despite their potential. This study aims to analyze and evaluate the impact of various rotor-pole combinations on the electromagnetic performance of 3-phase OR-HEFSMs. JMAG Designer is utilized to simulate and compare the electromagnetic behavior of multiple configurations, focusing on key parameters such as torque output, cogging torque, and flux linkage. The analysis explores the influence of both integer and fractional rotor-pole combinations, providing insights into their advantages and trade-offs. Furthermore, this research investigates techniques to reduce cogging torque, a primary source of torque ripples and noise in FSMs. Structural techniques such as chamfering, notching, and pole pairing were implemented, yielding critical design insights into rotor pole optimization for OR-HEFSMs. These findings support the future development of high-performance machines for electric mobility and renewable energy applications.